MRI detected prevalence of abnormalities in patients of knee pain - Mehta, Ritu; Agrahari, Neha Singh; Agarwal, Sanjeev; Bhargava, Abhishek (International Journal of Research in Medical Sciences, 2017)
Background: In patients of knee pain diagnosis has utmost important for treatment and to avoid unnecessary surgery. MRI is a non-invasive procedure in evaluation of knee joint. So this study was planned find out the prevalence of abnormalities detected by MRI in patients of knee pain. Methods: Fifty patient of knee pain were examined after taking permission from institutional ethics committee by using Siemens Avanto MR machine with a superconducting magnet and field strength of 1.5 tesla using dedicated knee coil (Flex), which were referred from department of Orthopedics & Rheumatology. Results: In this present study 72% patients were males and 28% patients females and their ages ranging from (11-80) years. Knee pain was found common in age group 31-40 years. Menisci lesions (44%) were more common as compared to ligament lesions (14%) in patients of knee pain. Osteoarthritis was found in 40 % of patients of knee pain. Joint effusion and marrow edema was found with incidence of 74% and 62% respectively. 4% patients were suffering from intraarticular tumors. Conclusions: Knee pain can occur at any stage of life due to various causative factors. MRI can demonstrate the exact nature and extent of bony as well as soft tissue abnormality. This has increase the use of MRI in evaluation of patients of knee pain.